Comparative analysis of pure CO2 and CO2 enhanced polymer flooding: a numerical modelling approach - Surajo Muhammed Gwio; Ousmane Soumah (African Scientific Reports, 2025)
In this research, the mechanism of pure CO2 flooding and that of CO2 enhanced polymer flooding were studied, and their efficiencies as they relate to recovery efficiency, displacement sweep e ciency, oil cumulative recovery, etc., were compared. CMG software was used for the modelling of the EOR techniques herein and STARS simulator was the platform of choice. The results obtained from the simulation studies have shown the CO2 enhanced polymer flooding to have superior overall oil recovery efficiency of 53% as against the 33% obtained from the pure CO2 flooding model, thanks to the mobility improvement from the polymer addition. Moreover, the pure CO2 flooding has less oil displacement sweep efficiency ranging between (40-45%), on the other hand, the CO2 enhanced polymer showed a significant improvement (70-75%). In the aspect of cumulative oil production, we were able to achieve 1.6 million barrels of oil from the CO2 enhanced polymer, greater than the 930 thousand barrels recorded from the pure CO2 flooding. Judging from the results of our analysis, it can be concluded that CO2 enhanced polymer flooding should be deployed on a larger scale for medium to low viscosity oil reservoirs, as against the use of pure CO2 flooding. Furthermore, CMG software has been shown to be effective and efficient software for modeling EOR processes.